REPRODUCTIVE PORTRAIT OF MEDICAL UNIVERSITY STUDENTS - Светлана Ивановна Елгина; Олеся Юрьевна Михальцова; Николай Владимирович Журин; Елена Владимировна Рудаева; Кира Борисовна Мозес; Вадим Гельевич Мозес; Наталья Степановна Черных (Medicina v Kuzbasse, 2023)
Student age is one of the critical periods in the biological, mental and social development of a person. Medical university students are insufficiently informed about reproductive health, STIs, and quite often use ineffective and unreliable methods of contraception. In combination with the widespread spread of gynecological diseases in girls, as well as the lack of preventive measures aimed at reducing gynecological pathologies and improving health, we can expect a decrease in the reproductive potential and fertility of the younger generation. Students of medical universities are at risk of fertility decline due to the influence of additional negative factors: stress, physical inactivity, lack of adequate nutrition, intellectual stress.